Impact of COVID-19 on Cytomegalovirus Immunoglobulin M Antibody Index - Masatoki Kaneko; Junsuke Muraoka; Li Yang; Shuichi Tokunaga; Toshio Minematsu (IMR Press, 2023)
Background: Coronavirus disease 2019 (COVID-19) influenced the prevalence of other infectious diseases, including congenital cytomegalovirus (CMV) infection. However, the effect of COVID-19 on antibody titers has not been reported. This study aimed to explore the influence of COVID-19 on levels of CMV immunoglobulin M (IgM) in pregnant women. Methods: This cross-sectional study included pregnant women who visited the University Hospital due to CMV IgM positivity during the 7th and 8th waves of COVID-19. Data, including maternal characteristics, history of COVID-19, CMV immunoglobulin G (IgG) and IgM index, and IgG avidity index (AI) were collected. Chemiluminescent immunoassay was performed to measure levels of IgG and IgM. Polymerase chain reaction using neonatal urine was performed to confirm congenital infection. Results: Of the 89 pregnant women, 36 (40%) (low IgG AI: n = 10; high IgG AI: n = 26) contracted COVID-19. Among 21 women with low IgG AI, 9 (false IgM positive: n = 8; primary infection: n = 1) had an IgG AI of 0. Among the eight women with false IgM positivity, six (75%) contracted COVID-19. The IgM index of pregnant women with false IgM positivity was 12.6 ± 10.9. Meanwhile, the CMV IgM index of pregnant women with false IgM positivity in the non-COVID-19-infected group was 1.7 ± 0.5. When the IgM indices of women who contracted (n = 36) and did not contract (n = 53) COVID-19 were compared, the IgM index of infected women (4.4 ± 5.7) was higher than those of non-infected women (2.7 ± 3.0) (p = 0.01). Regarding IgM and IgG AI, multiple logistic regression analysis revealed that there were no significantly different variables between the two groups. Conclusions: High prevalence of false IgM positivity was observed among women who contracted COVID-19. The IgM index of pregnant women with false IgM positivity was high. Caution should be exercised in interpreting CMV IgM indices in pregnant women with a history of COVID-19.